The different perspectives of sense of belonging in K. S. Maniam's the return and Gurcharan Das's a fine family - Mani, Manimangai (Scottish Journal of Arts, Social Sciences and Scientific Studies, 2016)
Sense of belongingness is a psychological condition which is caused, mainly by displacement.Displacement occurs when a specific cultural population is moved from its original homeland or bioregion and relocated to a different setting. There are many reasons that contribute to this phenomena and one of it is colonisation. In the quest for power and wealth, the British caused mass displacement of people in the countries that they colonised. They were either voluntarily displaced or forcefully moved away from their motherland into another British colony; all in the name of enhancing the economical growth and strengthening the political valor of the British Empire. This study will look into two groups of people who were displaced during the British colonial period. K.S. Maniam’s, The Return (1981) is about a South Indian family that is displaced in an alien land, British Malaya while Gurcharan Das’s novel,A Fine Family (1990)chronicles the life of a Punjabi Hindu family that is displaced in the same nation (the sub -continent of India) due to political partitioning. Both novels share the same time setting whereby both countries were still under the British colonisation. This study aims to distinguish the demonstration of sense of belongingness by the characters in these two novels. The demonstration of belongingness is an emotional self defence mechanism which prevails involuntarily among the displaced people. It is a mechanism that enhances self esteem and camouflages the emotional scars that comes together with any form of displacement. But the demonstration of sense of belongingness is never a set of fixed act. Instead, it varies with different variables that marked the displacement. This study will show how the difference in the nature of displacement co-relates with the different ways the victims react in establishing sense of belongingness to the new place.